Mendesain Grafis Lingkungan untuk Golden Harbour New International Ferry Terminal - Hengky Dwi Putra; Ria Sapitri (Puslitabmas Batam Tourism Polytecnic, 2022)
Batam is a strategic city. There is an international port that connects Batam City with neighboring countries. One of the ports under construction is the Golden Harbor New International Ferry Terminal. In this design, research was conducted based on surveys and observations. The experimental study method was carried out based on the results and observations and interviews were used in the process of making the design concept. Due to the new port, this is where the role of environmental graphic design will take part, namely as a supporter in identifying the direction and location of this new building or commonly referred to as wayfinding. The outputs of this design include system areas such as zoning, directions, and building locations, circulation paths, and information content, as well as marker designs in the form of information panels, object panels, and directional signs.